2004
DOI: 10.1128/iai.72.1.94-105.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of the C-Terminal Lysine Residues of Streptococcal Surface Enolase in Glu- and Lys-Plasminogen-Binding Activities of Group A Streptococci

Abstract: Streptococcal surface enolase (SEN) is a major plasminogen-binding protein of group A streptococci. Our earlier biochemical studies have suggested that the region responsible for this property is likely located at the C-terminal end of the SEN molecule. In the present study, the gene encoding SEN was cloned from group A streptococci M6 isolate D471. A series of mutations in the sen gene corresponding to the C-terminal region ( 428 KSFYNLKK 435 ) of the SEN molecule were created by either deleting one or more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
130
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(135 citation statements)
references
References 49 publications
3
130
2
Order By: Relevance
“…The binding region (amino acids 91-102) is located directly after the predicted transmembrane domain of the protein (www.cbs.dtu.dk/services/TMHMM/). M. pneumoniae PDHB shows a C-terminal lysine which was characterized as a potential binding region in enolase (Derbise et al, 2004), but no interaction of the corresponding recombinant protein derived from this region with human plasminogen was found. In contrast, the plasminogen-binding peptide identified has no lysine, indicating lysineindependent interactions between the two proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding region (amino acids 91-102) is located directly after the predicted transmembrane domain of the protein (www.cbs.dtu.dk/services/TMHMM/). M. pneumoniae PDHB shows a C-terminal lysine which was characterized as a potential binding region in enolase (Derbise et al, 2004), but no interaction of the corresponding recombinant protein derived from this region with human plasminogen was found. In contrast, the plasminogen-binding peptide identified has no lysine, indicating lysineindependent interactions between the two proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, enolases interact with plasminogen but binding to fibronectin and laminin has also been reported (Carneiro et al, 2004;Castaldo et al, 2009;Donofrio et al, 2009). The M. pneumoniae enolase shows typical putative plasminogen-binding sites, such as lysine in the C terminus, 448 FKNIK 452 , and a lysine-rich internal motif, 268 KRYVFKKGIKAKILDEK 284 (Bergmann et al, 2003;Derbise et al, 2004;Yavlovich et al, 2007). A surprising fact was the absence of this enzyme on the surface of mycoplasma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PspC and the PspClike protein Hic have been shown to interact with complement factor H (Dave et al, 2004;Janulczyk et al, 2000). Many pathogenic bacteria also produce receptors for Abbreviations: GAPDH, glyceraldehyde-3-phosphate dehydrogenase; GMFI, geometric mean fluorescence intensity; immuno-FESEM, field emission scanning immunoelectron microscopy; PspA, PspC, pneumococcal surface protein A or C. The plasminogen-binding motifs in the enolase enzyme were initially traced to C-terminal lysine residues (Bergmann et al, 2001(Bergmann et al, , 2004aDerbise et al, 2004). However, a subsequent study identified a nine residue internal plasminogen-binding site in enolase .…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the analyses have identified a significant number of traditional cytoplasmic proteins commonly thought to be intracellular in streptococci. Many of these proteins have been identified as virulence factors in streptococci, such as the glycolytic pathway enzymes enolase and GAPDH, which have been identified as plasminogen binding and cell wall-associated in S. pyogenes [125][126][127] and in S. pneumoniae [128].…”
Section: Anchorless Proteinsmentioning
confidence: 99%